Lasers and nevus of Ota: a comprehensive review. Issue 1 (January 2016) - Shah, Vidhi; Bray, Fleta; Aldahan, Adam; Mlacker, Stephanie; Nouri, Keyvan
Abstract Nevus of Ota is a benign dermal melanocytic nevus that typically affects Asian children and women. The nevus presents as unilateral blue-gray hyperpigmented macules and patches scattered along the first and second divisions of the trigeminal nerve. Individuals with nevus of Ota experience emotional and psychosocial distress related to cosmetic disfigurement and often look for treatment options. Unfortunately, even when treated early, lesions of nevus of Ota are still difficult to treat. The use of lasers for the treatment of nevus of Ota lesions has become helpful in the management of dermal nevi. Currently, Q-switched (QS) lasers have been the most studied and demonstrated positive results for treatment of nevus of Ota. The purpose of this review article is to summarize the clinical efficacy and side effects associated with QS lasers and the treatment of nevus of Ota lesions.